REVITALISASI LUMBUNG PANGAN MELALUI PEMBERDAYAAN KELOMPOK TANI DI KABUPATEN SELUMA PROPINSI BENGKULU - Priyono, Basuki Sigit; Sriyoto, Sriyoto; Yuliarso, M. Zulkarnain (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
The objective of this research are to assess farmers' perceptions about the food barn revitalization of farmer groups and determine the relationship between rice farmers attributes with their perception of the food barn revitalization. This research was conducted in the subsdistrict of Northern Seluma and Sukaraja, district of Seluma, in 2013. This research used primary and secondary data. Analysis method used in this research were qualitative descriptive and linear probability model analysis. The research resulted that farmers’ perception of the food barn revitalization is a good perception i.e. 89%. The land area and capital attributes were correlated significantly with the farmers’ perception, whereas age, formal education, farming experience, the sum of family burden, meeting frequency, cosmopolitan, and technology information searching were not correlated significantly.